Reanimating Qohelet's contradictory voices : studies of open-ended discourse on wisdom in Ecclesiastes - Kim, Jimyung (Biblical interpretation series, 2018)
"Ecclesiastes, also known as Qohelet, is a fascinating text filled with intriguing contradictions, such as wisdom's beneficial consequences, God's justice, and wisdom's superiority over pleasure. Under the paradigm of modernism, the contradictions in the book have been regarded as problems to be harmonized or explained away. In Reanimating Qohelet's Contradictory Voices, Jimyung Kim, drawing on Mikhail Bakhtin's insights, offers an alternative reading that embraces the contradictions as they stand. For Kim, Qohelet's or the protagonist's contradictory consciousness is dialogically constructed by his contact with a complex web of discourses. Instead of harmonizing them or explaining them away, Kim identifies various dialogic voices available to Qohelet and demonstrates how those voices constitute Qohelet's contradictory utterances and construct his unfinalizable identity"--